Analisis Konsumsi Energi dan Protein Menu Makan Siang Siswa Program Kelas Mandiri SMKN II Subang - Tuti Gantini; Hendrawan Hendrawan; Ardi Mulyono (AGRITEKH (Jurnal Agribisnis dan Teknologi Pangan), 2023)
Nutritional adequacy is an average adequacy of nutrients each day for people according to their age, gender, body size, body activity to reach the optimum health. Research to analize protein and energy consumption at lunch which was served for Mandiri class students of SMKN 2 Subang had been done. The objective of the research was to measure the adequacy of calory and protein intake of the students of SMKN 2 Subang based on menu plan. Menu was arranged for the cycle of 10 days. The descriptive method was applied in this research to find out the amount of energy and protein intake from lunch compared to the adequacy level that was recommended. Result of the analysis showed that contribution of protein from lunch compare to the recommended nutritional adequacy was 20.60% to 100.4%. Lunch menu at day 8th consisted of rice, stir-fried spinach and corn, and fried mujair fish contributed protein of more than 80%, and the contribution of protein was 19.88% to 31.42% that was less than the recommended adequacy level.